2020
DOI: 10.1177/2210491720978985
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic obturator–anterior type dislocation of the hip with an ipsilateral ischial tuberosity and greater trochanter fractures: Case report

Abstract: Anterior hip dislocation is a rare orthopedic emergency, usually following high-energy trauma. This injury is occasionally associated with acetabular fractures, femoral head fractures, or diaphyseal femoral fractures. However, the combination between the anterior hip dislocation and the ipsilateral ischial tuberosity and greater trochanter fractures is extremely rare, and very sparsely reported in the literature. This paper reports a case of an obturator type of anterior hip dislocation associated with a conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In other series, Selvanayagam and Vivek fixed greater trochanteric fracture with 6.5 mm screw fixation in his case report and produce full range of hip motion without any evidence of osteonecrosis or osteoarthritis at one year follow up [16] [17]. Concha et al reported a case of obturator type hip dislocation with greater trochanteric avulsion fracture treated successfully with tension band wiring and produce Harris Hip Score of 89 at 1-year postoperative period [18]. Akash and Subawa in their series of anterior hip dislocation with greater trochanteric avulsion utilised proximal femoral plate for fixation and achieved satisfactory outcome at 4 months' postoperative period using Modified Merle d'Aubigne Score and Oxford Hip Score.…”
Section: Discussionmentioning
confidence: 99%
“…In other series, Selvanayagam and Vivek fixed greater trochanteric fracture with 6.5 mm screw fixation in his case report and produce full range of hip motion without any evidence of osteonecrosis or osteoarthritis at one year follow up [16] [17]. Concha et al reported a case of obturator type hip dislocation with greater trochanteric avulsion fracture treated successfully with tension band wiring and produce Harris Hip Score of 89 at 1-year postoperative period [18]. Akash and Subawa in their series of anterior hip dislocation with greater trochanteric avulsion utilised proximal femoral plate for fixation and achieved satisfactory outcome at 4 months' postoperative period using Modified Merle d'Aubigne Score and Oxford Hip Score.…”
Section: Discussionmentioning
confidence: 99%